Controllable fabrication of micro/nanostructures by electrospinning from polystyrene/poly(vinyl alcohol) emulsion dispersions. Issue 26 (10th March 2018) - Cao, Ding; Li, Xinhua; Yang, Lixia; Yan, Dongpeng; Shi, Yan; Fu, Zhifeng
ABSTRACT: In this article, controllable micro/nanostructures were successfully obtained by electrospinning with the emulsion dispersions of polystyrene and poly(vinyl alcohol) (PS/PVA). The micro/nanostructure of electrospun PS/PVA emulsion dispersions such as corn‐like, spindle‐like, and bowl‐like (or bracelet‐like) were precisely controlled by regulating the electrospun parameters including the surfactant, the applied voltages, and the compositions of PS/PVA emulsion dispersions. The non‐ionic surfactant (Poloxamer) was crucial for the stability of the PS/PVA emulsion dispersions although the surfactant in PS/PVA emulsion was in tiny amount. The high applied voltages were beneficial for the forming the "lined‐fiber" structure but not for spheroids structure (bracelet‐like structure). Moreover, the increasing content of PS in PS/PVA emulsion resulted in more spheroid structure than the "lined‐fiber." This work was meaningful for the forming mechanism of micro/nanostructure in emulsion electrospinning and made a potential contribution for controllable fabrication of micro/nanostructure of the electrospun PS/PVA emulsion dispersions. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46288. Abstract :